2020
DOI: 10.3390/ani10122400
|View full text |Cite
|
Sign up to set email alerts
|

Linking Human Perceptions and Spotted Hyena Behavior in Urban Areas of Ethiopia

Abstract: Humans have shaped carnivore behavior since at least the Middle Paleolithic period, about 42,000 years ago. In more recent times, spotted hyenas (Crocuta crocuta) in Ethiopia have adapted to living in urban areas, while humans have adapted to living with hyenas. Yet, relationships between coexisting humans and carnivores are rarely addressed beyond mitigating conflicts. We provided a case study for how to broadly think about coexistence and how to study it when measuring if humans and carnivores affect one ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
(77 reference statements)
1
19
0
Order By: Relevance
“…However, studies on local people's perceptions and attitudes toward carnivore population abundance and trends, as well as conservation, are either scarce or, if available, species‐specific and limited to protected areas. To date, studies on attitudes toward carnivores in Ethiopia have been biased toward the spotted hyena ( Crocuta crocuta ), Ethiopian wolf ( Canis simensis ), and lion ( Panthera leo ) (Gebresenbet, Baraki, et al, 2018; Yirga et al, 2014; Young et al, 2020). Furthermore, the majority of recent wildlife studies have focused on herbivores (Abraham & Simon, 2020; Yosef, 2015), as well as conflicts between humans and wildlife in national parks (Biset et al, 2019; Mekonen, 2020; Merkebu & Yazezew, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on local people's perceptions and attitudes toward carnivore population abundance and trends, as well as conservation, are either scarce or, if available, species‐specific and limited to protected areas. To date, studies on attitudes toward carnivores in Ethiopia have been biased toward the spotted hyena ( Crocuta crocuta ), Ethiopian wolf ( Canis simensis ), and lion ( Panthera leo ) (Gebresenbet, Baraki, et al, 2018; Yirga et al, 2014; Young et al, 2020). Furthermore, the majority of recent wildlife studies have focused on herbivores (Abraham & Simon, 2020; Yosef, 2015), as well as conflicts between humans and wildlife in national parks (Biset et al, 2019; Mekonen, 2020; Merkebu & Yazezew, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The two most common conservation strategies are establishing protected areas to separate carnivores from human‐dominated areas (Srivathsa et al, 2019; Tilman et al, 2017) and promoting human–carnivore coexistence (HCCo): a sustainable state in which humans and wildlife co‐adapt to living in shared landscapes (Penjor et al, 2021; Teixeira et al, 2021; Western et al, 2019; Young et al, 2020). However, protected areas and native forests are rapidly diminishing as a result of anthropogenic habitat loss, forcing carnivores to local extinction or to share habitats with humans (Athreya et al, 2020; IUCN, 2021; Mekonen, 2020; Merkebu & Yazezew, 2021; Tamrat et al, 2020; Worku & Girma, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified boldness as a key trait for urban predators ( Breck et al, 2019 ; Brooks, Kays & Hare, 2020 ). Bold predators are more likely to approach and interact with novel objects and less likely to be disturbed by human presence, thus increasing the likelihood of discovering new foraging opportunities ( Young et al, 2020 ). However, bold predators may also experience reduced survival because they are more likely to incite human-wildlife conflict ( Greenberg & Holekamp, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, bold predators may also experience reduced survival because they are more likely to incite human-wildlife conflict ( Greenberg & Holekamp, 2017 ). Therefore, boldness may not only correlate to accessing resources but also human perceptions of wildlife ( Young et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…FID is generally defined as "the distance at which an animal moves away from an approaching threat" (Blumstein 2003). Thus, FID is a measure of antipredator behaviour that reflects the tolerance towards approaching threats, such as humans (Møller et al 2013;Cooper and Blumstein 2015;Young et al 2020), and employed in this study to understand the impact of human activity on bush squirel's behaviour. There are several applications of FID by wildlife managers.…”
Section: Introductionmentioning
confidence: 99%